Predicting aquaculture potential of an essential shrimp via species distribution models in China under climate change - Jie Wei; Yakun Wang; Kunhao Hong; Qiaoyan Zhou; Xinping Zhu; Caihong Liu; Lingyun Yu (Aquaculture Reports)
Aquatic products are a crucial component of global food systems, and the impacts of climate change on aquaculture are becoming increasingly significant. Thus, it is essential to rigorously evaluate the sustainability of aquatic food production in the face of climate change. This study investigates the potential effects of climate change on the aquaculture of the freshwater shrimp Macrobrachium rosenbergii in China, using advanced species distribution models (SDMs). By compiling a comprehensive dataset of aquaculture sites across China, we developed a robust set of SDMs to predict the suitability of aquaculture regions under both current and future climate scenarios. Our models demonstrated high predictive accuracy, revealing that the distribution of suitable aquaculture areas for M. rosenbergii is primarily determined by extreme temperature variations during the warmest and coldest months. Under present climate conditions, these areas are concentrated in eastern and southern China. However, projected climate changes could significantly reduce suitable regions, with losses ranging from approximately 6.00–29.11 %. These results highlight the critical need to consider the long-term effects of climate change when developing strategic plans for aquaculture management and production in China.